Stabilitate și schimbare în nivelurile și structura bunăstării subiective: România 1997-1999 - Bălțătescu, Sergiu (Calitatea Vieții, 2007)
One of the most important challenges to the contemporary social research is the modelling of change. This domain fully benefited from the availability of the social indicators, statistical time series used to monitor the social state and to anticipate change. The purpose of this paper is to explore aspects linked to the stability of the subjective well-being, one of the most important social indicators, defined as the evaluation of its life as an individual, in terms of good and bad. A moderate (but not total) stability is essential, showing that this variable is not a totally stable trait or a momentary disposition, but that it is sensible to change. The stability can be assessed in relative and absolute terms, and refers to the average levels or to the structure of the variable. These characteristics have been explored using a panel survey on 800 subjects, issued in the framework of the Romanian Quality of Life Diagnosis between 1997 and 1999. I found that the subjective well-being average levels significantly modifies with time. On the contrary, its structure (analyzed as the factorial configuration of 18 satisfaction and evaluation indicators, referring to most relevant domains of life, and the levels of their contributions to the variation of the overall satisfaction indicator) maintains its similarity across years. Besides their theoretical value, the results strongly argue against those who reject the study of the happiness and satisfaction, considering it as irrelevant for the social change.